Porosity of sol-gel silica glasses doped by ruthenium bipyridyl as measured by positron annihilation lifetime spectroscopy and nitrogen adsorption - Reisfeld, Renata; Zigansky, Elena; Jasińska, Bożena; Wodnicka, Krystyna (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
The porous structure of glasses incorporated by ruthenium tris bipyridyl chloride (further Rubpy) and adsorbed by Rubpy is studied by positron annihilation lifetime spectroscopy and liquid nitrogen adsorption method. The first method provides the radius of the pores in the range of 0.6–4 nm and their distribution. The second method provides the radius of the pores in the range of 1–150 nm, their total volumes, size distribution and specific surface area. In the first method both closed and opened pores can be seen when the measurements are made on bulk samples as in this work. When thin films are measured, one has to use a capping material to prevent backscattering. The dimension of the pores can be controlled by the catalyst used for sol-gel formation. When Rubpy is prepared by adding its salt to precursor solution catalyzed by HCl, the pore size increases because of stress exhibited by large molecules. The pore size decreases with adding of Rubpy in precursor solution, catalyzed by HF and HNO3. Glass doped by Rubpy is less sensitive to the type of catalyst, than undoped glasses. A comparative study was performed on undoped glasses prepared by the identical method. We shall discuss the similarities and differences of the two methods.
Optica Applicata, Vol. 35, 2005, nr 4, s. 677-689
Keywords: optyka; porous glasses; ruthenium tris bipyridyl chloride; pore size; liquid nitrogen adsorption method; positron annihilation lifetime spectroscopy